The Beautiful and the Sublime in Wordsworth's Poem I Wandered Lonely as a Cloud (1807) - Hunar Shah; Asma Rahim; Haseena Rahim, (Dialogue Social Science Review (DSSR), 2024)
The approach is relevant to explore some specific perspectives on the poetry by giving close reading to the poem I Wandered Lonely as a Cloud as well as looking at the poem historical backdrop. Each theoretical method enables us to notice aspects of the poem that we might otherwise overlook. The first interpretive lens, and the one that will be focused on this poem, is to examine the poem in relation to Immanuel Kant and Edmund Burke’s aesthetic views. Wordsworth, a key figure in Romantic literature, expresses Romantic Aesthetics through a deep connection with Nature, emphasizing emotions, imagination, and individual experience. This article aims at investigating the beautiful and the sublime according to Kantian and Burkean concepts of Aesthetics. The initial findings reveal that Wordsworth celebrates the beautiful and the sublime in the poem. Wordsworth believes in the transformative power of Nature to evoke profound emotions and inspire a sense of awe, reflecting the romantic emphasis on the subjective and emotional aspects of human experience. This research is qualitative. Wordsworth’s poem I Wandered Lonely as a Cloud is the first source of data collection. Books and research articles are secondary sources of data collection. Research approach is inductive. This poem can further be analysed from the perspectives of other philosophers of Romantic Aesthetics.